Strategi Komunikasi Guru Dalam Menerapkan Pendidikan Karakter Terhadap Kelas IX Fullday di SMP Muhammadiyah 7 Medan - Rahmad Nurdiansyah; Effiati Juliana Hasibuan; Novri Novri (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
This study aims to determine the teacher's communication strategy in implementing character education, monotheism, courtesy and courtesy as well as discipline toward students of class fullday in SMP Muhammadiyah 7 Medan. The research method used by researchers in this research is descriptive method with qualitative analysis. The results obtained by the study that the first informant is the teacher uses a communication strategy approaching the Middleton communication strategy theory: (1) Tawheed character, communication strategies in implementing tawheed character education, communicators by taking into account the credibility of the source and then managing the class by attracting the attention of students by saying greetings and ask the students 'situation, the message conveyed is the material of monotheism rububiyah, uluhiyah and al asma' was shifat explained verbally and non-verbally using standard Indonesian and the latest language terms; (2) polite and polite characters, communication strategies in implementing polite and polite character education by paying attention to the credibility of the source, managing the class get the attention of students by calling two or more students to the front of the class to demonstrate the form of interaction of polite and polite characters that have an element of cuteness, a message that be delivered; (3) Discipline character, communication strategies in implementing disciplinary character education that is communicators pay attention to the credibility of the source, then get the attention of students by conducting questions and answers there are elements of jokes about the form of discipline of daily activities that are both useful or not.